Ethics and Sustainable Management. An Empirical Modelling of Carroll’s Pyramid for the Italian Landscape - Ernesto D’Avanzo (MDPI AG, 2021)
Business management and, more generally, decision makers, are increasingly aware of the importance of corporate social responsibility and ethical choices within the strategic business vision. The number of tools (e.g., board of directors, organization actions), levers (e.g., cultural, social example of direct boss) and rules (e.g., protocols, certifications, law decrees) available, however, makes it difficult for management to identify the set of best practices to be adopted within its own organization. Further, the task is even more difficult when management is called upon to choose these tools for life-long learning programs intended for company staff as well as for new hires. The Italian Association for Managerial Training has promoted a survey that pays particular attention to the «ethical choices» and «behaviors» to be adopted in the organization’s management and their training programs. The results of the survey have been modelled through «Carroll’s conceptual framework» that, as known, is made of two parts: the most cited CSR pyramid and the least mentioned, but equally important, descriptive types of management. In this work, it has been employed a two steps multivariate analysis, employing an Exploratory Factor Analysis (EFA) and a Structural Equation Modelling (SEM). EFA has been used to identify Carroll’s descriptive types (or profiles), while SEMs were employed to verify the plausibility of the causal models that represent, in turn, thought experiments simulating «ethical dilemmas» useful for the company’s management during its decision making. The models identified, readable in the form of simple «heuristics», are interpreted in the light of Carroll’s «descriptive types» of management (i.e., moral, immoral and amoral). Thereby, any organization, even of a small size, interested in adopting «sustainable policies», can make use of the identified models to establish which guidelines can be adopted by the management during her/his decision making, and, according to Carroll, «to isolate the ethical or moral component of CSR and relate it to perspectives that reflect the three major ethical approaches to management», with the overall objective of managing with «stakeholders in an ethical or moral fashion».